2017
DOI: 10.1021/jacs.7b07598
|View full text |Cite
|
Sign up to set email alerts
|

Step-Economical Photoassisted Diversity-Oriented Synthesis: Sustaining Cascade Photoreactions in Oxalyl Anilides to Access Complex Polyheterocyclic Molecular Architectures

Abstract: Atom- and step-economy in photoassisted diversity-oriented synthesis (DOS) is achieved with a versatile oxalyl linker offering rapid access to complex alkaloid mimics in very few experimentally simple steps: (i) it allows for fast tethering of the photoactive core to the unsaturated pendants, especially important in the case of (hetero)aromatic amines-essentially a one-pot reaction with no isolation of intermediates; (ii) the α-dicarbonyl tether acts as a chromophore enhancer, extending the conjugation chain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…For practical reasons, it is primarily focused on accessing complex targets with high step‐economy and other economies of synthesis [3] . With modern calculable indices of molecular complexity, [4] the field moved from qualitative to quantitative narrative, and we suggested that step‐normalized increases of molecular complexity [5] could offer a more instructive measure of step‐economy of synthetic campaigns. We previously used a public domain resource DataWarrior [4d] to evaluate molecular complexity.…”
Section: Methodsmentioning
confidence: 99%
“…For practical reasons, it is primarily focused on accessing complex targets with high step‐economy and other economies of synthesis [3] . With modern calculable indices of molecular complexity, [4] the field moved from qualitative to quantitative narrative, and we suggested that step‐normalized increases of molecular complexity [5] could offer a more instructive measure of step‐economy of synthetic campaigns. We previously used a public domain resource DataWarrior [4d] to evaluate molecular complexity.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the side self‐reaction rate can be dramatically reduced, leading to a marked improvement of the yields, by slowing down the activation of DBF using a poorly soluble inorganic base (e. g., sodium bicarbonate) in organic solvents as dichloromethane, [49,50] THF [51] or ethyl acetate [52] . However, this reaction can be carried out also in more polar solvents such as water [40] and DMF [53,54] or using organic bases such as DBU [55] or TEA [56] . In this context, two interesting case studies on the effect of different bases and solvent have been carried out [51,57] .…”
Section: Synthesis Of 3‐halo‐45‐dihydroisoxazolesmentioning
confidence: 99%
“…35 Especially the generation of hetero aza-o-xylylenes (heteroatom analogue o-QDMs) was repeatedly used to enable elegant syntheses of complex structural motifs. [36][37][38][39] To the best of our knowledge, there is only one report that indicates the formation of o-QDMs using visible light: Furukawa…”
Section: -25mentioning
confidence: 99%
“…A large number of synthetically valuable transformations including light-induced reactions based on o -QDMs have been reported, including various organocatalytic strategies for enantioselective trapping of o -QDMs . Especially the generation of hetero aza- o -xylylenes (heteroatom analogue o -QDMs) was repeatedly used to enable elegant syntheses of complex structural motifs. To the best of our knowledge, there is only one report that indicates the formation of o -QDMs using visible light: Furukawa and co-workers reported in 1993 that 8,13-dihydrobenzo­[ g ]­naphtho­[1,8- bc ]­[1,5]­diselenonine forms o -QDMs under exposure of ambient laboratory light . This interesting reaction forms naphtho­[1,8- cd ]­[1,2]­diselenole in stoichiometric quantities, thus requiring chromatographic purification.…”
Section: Introductionmentioning
confidence: 99%